A Case of Lung Adenocarcinoma with Marked Improvement of Pulmonary Lymphangitic Carcinomatosis by Adding Bevacizumab to Cisplatin and Pemetrexed - Natsume, Maika (Case Rep Oncol, 2017)
A 40-year-old man with a diagnosis of lung adenocarcinoma (cT4N3M1c, stage IVB) experienced worsening of lymphangitic carcinomatosis in the right lung and right pleural effusion after receiving 1 cycle of first-line chemotherapy consisting of cisplatin and pemetrexed. Bevacizumab was thus added from the second cycle of the cisplatin-pemetrexed regimen, leading to a marked improvement in pulmonary lymphangitic carcinomatosis and a decrease in pleural effusion. Subsequently, maintenance therapy consisting of pemetrexed and bevacizumab was continued, successfully leading to long-term progression-free survival. Generally, pulmonary lymphangitic carcinomatosis shows poor prognosis because of poor response to chemotherapy. However, recent studies have been elucidating the role of the vascular endothelial growth factor A (VEGF-A)/VEGF receptor-2 pathway in pulmonary lymphangitic carcinomatosis. Therefore, bevacizumab is expected to be beneficial in the treatment of this pathological condition.